THE REACTION HUMAN BEHAVIOR TO NATURE IN DEAN DEVLIN’S MOVIE “GEOSTORM”: USING LITERARY ECOCRITICISM - Indrawan, Fajar; Nur, Sahril (Journal of English Literature and Linguistic Studies, 2025)
The Reaction Human Behavior to Nature in Dean Devlin's Movie “Geostorm” Using Literary Ecocriticism. English Department, Faculty of Languages and Literature, Makassar State University. Determining the types of human-nature relationships and the natural disasters shown in Dean Devlin's film "Geostorm" is the goal of this study. Because the purpose of this research is to explain the phenomena that occur in terms of language, a qualitative descriptive method is employed in this study. The conversation between characters from a number of scenes in the movie Geostorm served as the research's data source. Our applied Garrard's (2004) literary ecocriticism approach to data analysis. Determining the types of human-nature relationships and the natural disasters shown in Dean Devlin's film "Geostorm" is the goal of this study. Because the purpose of this research is to explain the phenomena that occur in terms of language, a qualitative descriptive method is employed in this study. The conversation between characters from a number of scenes in the movie Geostorm served as the research's data source. Our applied Garrard's (2004) literary ecocriticism approach to data analysis.